OPTIMIZING STUDENTS’ SELF REGULATED LEARNING THROUGH ENGLISH PRONUNCIATION APPLICATION IN LEARNING PRONUNCIATION DURING PANDEMIC ERA - Didih Faridah; Lilies Youlia Friatin; Dedeh Rohayati (JALL (Journal of Applied Linguistics and Literacy), 2022)
The use of mobile technology, especially MALL (Mobile Assisted Language Learning) grows popularly in pandemic era. Most of teacher use it to help students while they are learning at home. This study is aimed at interpreting students' perceptions towards the use of English Pronunciation application on students’ self-regulated learning and investigating the use of English Pronunciation application in optimizing their self-regulated learning in learning pronunciation. Researchers applied a qualitative case study as the research design of this study. The data were collected through questionnaires and interviews. This research involved 25 students of the freshman of English Education Program in a private university in Ciamis. The result shows that the students respond positively on the use of English Pronunciation application in learning pronunciation since it helped them in overcoming their problems in learning pronunciation, especially in pandemic era where they situated to learn at home. The results also indicate that the use of English Pronunciation application in learning pronunciation is effective to optimize students’ self-regulated learning.